Karakterisasi Material Biokomposit Bovine Hidroksapatit (BHA)/Shellac dan Kitosan Sebagai Material Bone Filler - Rasid, Junaidi; Triyono, Joko; Triyono, Teguh (ROTASI, 2017)
Development of composite materials is growing rapidly to support medical needs. Biocomposite was made from bovine bone powder/shellac/chitosan for bone filler applications. Biocomposite of BHA(Bovine Hydroxyapatite)/shellac/chitosan was derived of bovine bone powder coated with shellac 10 ml. Mixed variation between BHA/shellac and chitosan i.e 30:40, 40:60, 50:50, 60:40, 70:30 %wt  were synthesized by dry method. Samples of BHA/shellac/chitosan were compacted with the pressure 60 bar until becomes solid with the cylinder mold 13 mm and 8 mm in thickness, the calcination process on temperature of  900ºC for 2 hours and increased temperature is 10ºC/min. Test XRD (X-Ray Diffraction), Microvickers, DTS (Diametric Tensile Strength) and SEM (Scanning Electron Microschopy), Density, and Porosity. XRD test results showed that bovine powder has become BHA (Bovine Hydroxyapatite), microvickers test of sample BHA/shellac/chitosan for maximum was 7.47 ± 0.685 VHN and 0.182 ± 3.73 VHN for minimum, DTS test of sample BHA/shellac/chitosan maximum at 36.66 ± 9.01 KPa and minimum at 13.90 ± 1.24 KPa. Porous observations with SEM toward sample BHA/shellac/chitosan porous size and number of samples contained at BHA/shellac/chitosan is 70:30 wt%. Density test with  highest value was 1,168gr/cm3, and lowest 1,070 gr/cm3. Highest porosity value at variation 50/50 %wt = 0,988%, and the lowest at 70/30 %wt = 0,977%